Age-appropriate infant and young child feeding practices are associated with child nutrition in India: Insights from nationally representative data - Menon, Purnima; Bamezai, Apurva; Subandoro, Ali; Ayoya, Mohamed Ag; Aguayo, Victor (Wiley, 2015)
Age‐appropriate infant and young child feeding (IYCF) practices are critical to child nutrition. The objective of this paper was to examine the associations between age‐appropriate IYCF practices and child nutrition outcomes in India using data from ∼18 463 children of 0–23.9 months old from India's National Family Health Survey, 2005–06‐3. The outcome measures were child height‐for‐age z‐score (HAZ), weight‐for‐age z‐score (WAZ), weight‐for‐height z‐score, stunting, underweight and wasting. Linear and logistic regression analyses were used, accounting for the clustered survey data. Regression models were adjusted for child, maternal, and household characteristics, and state and urban/rural residence. The analyses indicate that in India suboptimal IYCF practices are associated with poor nutrition outcomes in children. Early initiation of breastfeeding and exclusive breastfeeding were not associated with any of the nutrition outcomes considered. Not consuming any solid or semi‐solid foods at 6–8.9 months was associated with being underweight (P < 0.05). The diet diversity score and achieving minimum diet diversity (≥4 food groups) for children 6–23 months of age were most strongly and significantly associated with HAZ, WAZ, stunting and underweight (P < 0.05). Maternal characteristics were also strongly associated with child undernutrition. In summary, poor IYCF practices, particularly poor complementary foods and feeding practices, are associated with poor child nutrition outcomes in India, particularly linear growth.